Anion‐π Interaction for Molecular Recognition of Anions: Focus on Cooperativity with Hydrogen Bonding. Issue 9 (13th December 2022) - Plais, Romain; Clavier, Gilles; Salpin, Jean‐Yves; Gaucher, Anne; Prim, Damien
Abstract: Anion recognition represents an active area of research in supramolecular chemistry. The last two decades have been marked by spectacular advances in the design of new anion receptors. Moreover, the development of approaches combining experimental and theoretical studies has proved to be particularly relevant, allowing for a better understanding and rationalization of the phenomena involved in anion complexation processes. In this context, the combination of weak interactions within the same receptor and their synergistic effects, called cooperativity, has attracted increasing interest within the scientific community. This Review focuses on the combination of anion‐π and hydrogen bonds and the emerging concept of cooperativity. The most relevant anion‐π donor families are presented. The concept of cooperativity is illustrated using the most recent examples present in current literature. Abstract : Hydrogen bonding and anion‐π interactions: two interactions of today's research in anion recognition supramolecular chemistry. The combination of these two interactions gives rise to interesting cooperativity effects that remain difficult to rationalize and quantify. In this Review, concepts of cooperativity are illustrated by reporting examples of combination of hydrogen bonding and anion‐π interaction.